Sustainability of Healthcare Financing in the Western Balkans : An Overview of Progress and Challenges - Bredenkamp, Caryn (World Bank, Washington, DC, 2012)
This paper explores the major challenges to the sustainability of health sector financing in the countries of the Western Balkans - Albania, Bosnia and Herzegovina, the Former Yugoslav Republic of Macedonia, Montenegro, Serbia and the province of Kosovo. It focuses on how the incentives created by the different elements of the healthcare financing system affect the behavior of healthcare providers and individuals, and the resulting inefficiencies in revenue collection and expenditure containment. The paper analyzes patterns of healthcare expenditure, finding that there is some evidence of cost containment, but that current expenditure levels - while similar to that in EU countries as a share of GDP - are low in per capita terms and the fiscal space to increase expenditures is extremely limited. It also examines the key drivers of current healthcare expenditure and the most significant barriers to revenue generation, identifying some key health reforms that countries in the sub-region could consider in order to enhance the efficiency and sustainability of their health systems. Data are drawn from international databases, country institutions, and household surveys.